KEPELOPORAN SAPARDI DJOKO DAMONO DAN HAMSAD RANGKUTI DALAM PEMBINAAN PENYAIR MUDA INDONESIA - Saksono Prijanto (LITERASI: Indonesian Journal of Humanities, 2014)
Great names of Jassin, Gunawan Mohammad, Sapardi Djoko Damono, and Mochtar Lubis as editors of Horizon, gave a quality assurance of literary magazine. However, it should be realized that the ratio of the number of literature pages and literary works was uneven. As a result, not all literary works can be published in Horizon literary magazine. Some newspapers such as –Suara Karya, Berita Buana, Pelita, Kompas, dan Sinar Harapan– provide a rubric of literature, for publishing literary essays and literary works (short stories and poetry). The limited space for literary works of young people to be published in literary magazines or literature section in a newspaper is unable to discourage the spirit of the young people to produce their works. Their hope are open with the presence of Sapardi Djoko Damono (poet) and Hamzad Rangkuti (short story writer) through the Indonesian Poetry Publishing Foundation. They argued that no one may prohibit the birth of a creative process, especially the literary works of the young people. Painstakingly, the two writers have read and selected poetry composed by young poets from all over Indonesia. Collection of poems that have been recommended by two great writers have been published in the form of simple physical (paper stencils) and funded by these young poets. Some of the young poets have published their poem anthologies through sponsorship of the local government of their origins or private companies. Keywords: literary magazines, poetry Indonesia, a young poet, sponsors, newspapers